Shaman Curing Ceremony - G.F. MacDonald Collection (1972)
Sadie Mowatt performs healing ceremony on Barlow Green. Ernest Hyzims with drum in the background. Among the Tsimshian, a shaman could be a man or a woman endowed with special powers. Shamans specialized in healing the sick, attracting fish or game, influencing the outcome of warefare, or predicting th eweather.